Tools to modify cherries harvest time in Alto Valle de Río Negro and Neuquén, Argentina - Raffo Benegas, Maria Dolores; Curetti, Mariela (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2021)
Cherry production is characterized by a very short fruit development period that covers an average of 80 days from flowering to harvest. Although there are varieties with different cycles, the harvest in Alto Valle de Río Negro and Neuquén, Argentina, is highly concentrated. The possibility of extending the harvest period allows to improve logistics, decongest packing work and regulate to a certain extent the supply of cherries on the market. Fruit cherries are highly perishable non-climacteric fruits and have low supply in counter season, which determines an unsaturated foreign market and the possibility to obtain good prices. The highest prices on the market depend on the fruit size and fruit quality and the harvest time (early and late). The aim of this work was to evaluate the feasibility of using different growth regulators and bio-stimulants to extend the sweet cherries harvest period. The use of hydrogen cyanamide (HC) in early varieties to advance the harvest and the use of Retard Cherry® (RCH) in late varieties to delay flowering and harvesting were evaluated. In addition, the effect of gibberellins (Gb) on the delay of maturity and improvement in quality in different varieties was evaluated. The use of HC allowed to advance bloom by 10 days and the harvest by 7 days in fruits of New Star, while RCH delayed the bloom (10 days) and maturity (5 days) of Santina, Lapins and Regina cherries. The application of Gb at 20 ppm from straw yellow stage until the start of the pink improves the quality of the fruits, but the effect on delaying maturity decreases with later applications. The use of regulators in cherries allows to extend the harvest window in nearly 10 days, depending on each cultivar and the meteorological conditions of the season.